EVALUASI SISTEM PENGENDALIAN MUTU BAHAN BAKU DAN PRODUK AKHIR UDANG BEKU DI PT. LESTARI MAGRIS PALEMBANG - Riyadi, Slamet (Faculty Fisheries Departement Fisheries, 2003)
Quality of a product will determine the market price. The better quality it has the higher the price it will be. To get good quality for frozen shrimp product, the company should do the quality control starting from acquiring the raw material until processing the frozen shrimp product. The objective of this study was to investigate the quality control system of frozen shrimp product at the PT. Lestari Magris Palembang. The data analysis was done by using the P control chart, to examine whether the 2nd quality source received by the company is still acceptable or not. Furthermore, it was also done to evaluate the data of the result of final product test for frozen shrimp to determine whether it fulfill the standard quality to be exported or not. The P control chart showed the amount of defect with size (n) was not constant. The upper level control (BA) = , medium are (GT) = and lower level control (BB). Based on the analysis it shows that 2nd quality for FWS, Pink, Tiger, White, and FSS shrimp received by the company was beyond the control, while for the 2nd quality of Cat Shrimp was within the control. For the 2nd quality shrimp, which received has good quality to raise the income of the company and the supplier as well. The result of the final product evaluation of frozen shrimp, which was produced by the company, showed that the product has fulfilled the standard of quality to be exported.Keywords : Quality Control System